The WEST project: validation program for WEST tungsten coated plasma facing components. (13th January 2016) - Richou, M; Missirlian, M; Tsitrone, E; Bucalossi, J; Desgranges, C; Firdaouss, M; Guilhem, D; Greuner, H; Hernandez, C; Lipa, M; Pintsuk, G; Samaille, F
Abstract: The W—for tungsten—Environment in Steady-state Tokamak (WEST) project is based on an upgrade of the Tore Supra tokamak from a carbon limiter to an X -point divertor device. A new set of actively cooled tungsten coated plasma facing components will cover a part of the vessel to provide a fully metallic environment. This paper deals with the validation program performed for tungsten coatings (≥15 μ m) on a CuCrZr substrate. The first step was dedicated to the qualification under high heat flux tests of the coating on small inertially cooled samples. To study the thermal behavior and the non-uniformity, the second step was dedicated to the validation of the coating on large inertially cooled samples with geometry and shape (540 × 120 mm) representative of the WEST coated components. The last step was dedicated to the optimization of the coating and to the high heat flux tests up to 10.5 MW m −2 on relevant coated actively cooled prototypes. Non-uniformity and thickness of the coating (15 and 30 μ m) correspond to specifications. As no delamination was observed, coatings of 15 and 30 μ m were qualified with regard to their application on WEST coated components. In order to decrease the risk of coating delamination under thermal loading, it was decided to cover the upper divertor and baffle targets with the thinnest coating option of 15 μ m.